USM CONTINUES TO SOAR UPWARDS - MPRC, Pusat Media & Perhubungan Awam (2017)
PENANG, 8 March 2017 – Universiti Sains Malaysia (USM) continues to soar upwards in the results of the QS World University Ranking by Subjects 2017 announced today, with the subject of Hospitality and Leisure Management, being listed for the first time in the QS rankings, positioned at number 32 in the world and the subject achieving the highest position from USM.